Ischemic conditions and β-secretase activation: The impact of membrane cholesterol enrichment as triggering factor in rat brain endothelial cells. (December 2015) - Brambilla, Anna; Lonati, Elena; Milani, Chiara; Rizzo, Angela Maria; Farina, Francesca; Botto, Laura; Masserini, Massimo; Palestini, Paola; Bulbarelli, Alessandra
Abstract: Among harmful conditions damaging the blood–brain barrier, cerebral stroke and reperfusion injuries were proposed as contributing factors to Alzheimer's disease etiology. Indeed it was reported that ischemic conditions promote β-amyloid peptide production in brain endothelial cells, although implicated mechanisms are yet not fully understood. Oxidative injury related to ischemia affects membrane-lipids profile by altering their biochemical properties and structural dynamics, which are also believed to play significant role in the amyloid precursor protein processing, suggesting a link between alterations in lipid membrane composition and β-amyloid peptide production enhancement. Using brain microvascular endothelial cells, here we demonstrate how oxygen and glucose deprivation followed by normal conditions restoration, mimicking ischemic environment, increases cell cholesterol amount (+20%), reduces membrane fluidity and results in strong activation (+40%) of β-secretase 1 enzymatic activity. Moreover, we observed an increase of amyloid precursor protein and β-secretase 1 protein levels with altered localization in non-discrete (Triton X-100 soluble) membrane domains, leading to an enhanced production of amyloid precursor protein β-carboxyl-terminal fragment. Therefore, lipid alterations induced by oxygen and glucose deprivation enhance β-secretase 1 activity, favor its proximity to amyloid precursor protein and may concur to increased amyloidogenic cleavage. The latter, represents a detrimental event that may contribute to β-amyloid homeostasis impairment in the brain and to Alzheimer's disease-related BBB dysfunctions.